Infertility and surrogacy first mentioned on a 4000-year-old Assyrian clay tablet of marriage contract in Turkey. (2nd January 2018) - Turp, Ahmet Berkiz; Guler, Ismail; Bozkurt, Nuray; Uysal, Aysel; Yilmaz, Bulent; Demir, Mustafa; Karabacak, Onur
Abstract: Mankind has been expressing the breeding topic for thousands of years. Reproduction is the primary instinct of human beings and it is a social, cultural, medical issue. Demographic infertility is one of them, which is defined infertility as the inability to become pregnant with a live birth, within five years of regular sexual contact based upon a consistent union status in marriage maintaining a desire for a child with the lack of contraceptive use and non-lactating. A first mentions about infertility and surrogacy is discovered on a 4000-year-old clay tablet of marriage contract belonging to the Assyrian period exhibited at Istanbul Archeology Museum in Turkey. In conclusion, there are many different ways to solve infertility problems like surrogacy as mentioned even 4000 years ago in this Assyrian clay tablet of marriage contract as the first time in the literature. Medical treatments in relation to human infertility will continue to be the focus of social and cultural debates. Hence, more legislation and regulation will come in many countries to control the unauthorized exploitation of the patient.